The effects of public spending on education, health and work on the performance of the FIRJAN Municipal Development Index in Cities in the State of São Paulo (Research, Society and Development, 2022)
This article evaluates the existing or non-existent correlations between public expenditures of government functions (Education, Health and Work) in São Paulo cities and the results of the FIRJAN Municipal Development Index (IFDM), using the statistical technique of discriminant analysis, in order to verify the influence of numerical variables (public expenditures) on a categorized variable (General IFDM), involving statistical tests, using the SPSS (Statistical Package for the Social Sciences) software. Essentially, it consisted of collecting information in the Brazilian Municipal Finance Database (FINBRA) regarding public expenditures carried out in the periods 2013 to 2016 (last data released in FINBRA) in 607 municipalities surveyed in the three government functions mentioned. Additionally, information on the population of each location was collected from the Brazilian Institute of Geography and Statistics (IBGE), as well as the results of the IFDM for each municipality, also in the years specified above, in the database of the Federation of Industries of Rio de January (FIRJAN). The results pointed to the inexistence of correlation between the expenses of the Education and Health government functions and the IFDM, with only the variable Expenditure – Education being significant for the model, that is, only it has an impact on the classification. It is suggested for future research that a discriminant analysis of the IFDM be carried out, separating the indices by their dimensions, relating to the government functions separately.